Pemikiran Filosofis Pendidikan Ibnu Sina Dan Implikasinya Pada Pendidikan Islam Kontemporer - Putra, Aris Try Andreas (Literasi: Jurnal Ilmu Pendidikan, 2015)
Abstract The central issue faced by the Muslim world, especially Islamic education today is the inception of secular science. Science is presented in the form of dichotomy. To pave the issue of Islamic education, the required reconstruction of the educational philosophy of Islam. In order to answer this question the author tries to present the ideas of Ibn Sina were rational religious scented. Ibn Sina is a figure of Islamic education which produces a lot of work in various fields of science, especially medicine and education, Ibn Sina emphasizes education was held by non-dichotomous. Educational purposes thinks should be directed towards preparing a person to be able to live in the community together with the conduct of expertise chosen according to their talents and potentials. Therefore, the curriculum is conceived by Ibn Sina conceived and developed based on the stage of growth and development of the Child. Keywords: Thinking Education, Ibnu Sina, and Implications